Editor's Preface - Denys Svyrydenko (International Society of Philosophy and Cosmology, 2023)
You are holding the second issue of the Future Human Image journal for 2023 in your hands. This challenging year for Ukraine passed under the sirens of the threat of missile attacks, and scientists were able to work thanks to the heroic resistance of the Armed Forces of Ukraine. Human civilization, on a large area of our planet, simultaneously moved toward establishing the priorities of sustainable development, Industry 4.0., and inalienable values, rights, and freedoms outlined in many international documents. The armed aggression, the victim of which is Ukraine, demonstrates that, in parallel, in human nature and the practice of political systems of totalitarian states, there remains an existential space for the actualization of the "dark side of human nature", which endangers the world order of peaceful coexistence, levels the value of human life in favor of the implementation of practices capture of territories, shows disdain for international law, implements practices of actual destruction of alternative, civilized social, cultural and political structures.